2023
DOI: 10.1186/s12893-023-02231-z
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors analysis of surgical site infections in postoperative colorectal cancer: a nine-year retrospective study

Cong Han,
Wei Chen,
Xiao-Li Ye
et al.

Abstract: Background Colorectal cancer (CRC) patients undergoing surgery are at a high risk of developing surgical site infections (SSIs), which contribute to increased morbidity, prolonged hospitalization, and escalated healthcare costs. Understanding the incidence, risk factors, and impact of SSIs is crucial for effective preventive strategies and improved patient outcomes. Methods This retrospective study analyzed data from 431 CRC patients who underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Numerous systematic reviews and meta‐analyses describe the link between diabetes and SSI 27–29 . Elevated blood glucose levels not only inhibit natural wound healing mechanisms by reducing collagen synthesis and disrupting angiogenesis, but also create an environment conducive to bacterial proliferation 30 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous systematic reviews and meta‐analyses describe the link between diabetes and SSI 27–29 . Elevated blood glucose levels not only inhibit natural wound healing mechanisms by reducing collagen synthesis and disrupting angiogenesis, but also create an environment conducive to bacterial proliferation 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous systematic reviews and meta‐analyses describe the link between diabetes and SSI. 27 , 28 , 29 Elevated blood glucose levels not only inhibit natural wound healing mechanisms by reducing collagen synthesis and disrupting angiogenesis, but also create an environment conducive to bacterial proliferation. 30 Pennington et al 27 demonstrated that persistent postoperative hyperglycaemia is a risk factor for deep wound infection after spinal surgery.…”
Section: Discussionmentioning
confidence: 99%
“…SSIs contribute to prolonged periods of postoperative fever, extended hospital stays and an increase in overall healthcare costs. The pathophysiological mechanisms underlying SSIs are multifaceted and often include microbial colonization at the surgical site, impaired local and systemic immune responses and a disruption in the gut microbiota, among other factors 3,4 …”
Section: Introductionmentioning
confidence: 99%
“…The pathophysiological mechanisms underlying SSIs are multifaceted and often include microbial colonization at the surgical site, impaired local and systemic immune responses and a disruption in the gut microbiota, among other factors. 3,4 Antibiotic prophylaxis is conventionally employed to minimize the risk of SSIs. While antibiotics are undeniably efficacious in curtailing infections, their usage is not without drawbacks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation